Tsunami Disaster Mitigation Study by Determining Run Up and The Banyuwangi Area Tsunami Arrival Time - Suriajaya Maha Putra, I Putu Agum; Suarbawa, Komang Ngurah; Putra Adnyana, I Gusti Agung (BULETIN FISIKA, 2021)
Tsunami disaster mitigation studies have been conducted in Banyuwangi Regency by conducting research on the analysis of run-ups and tsunami arrival times for the Banyuwangi area. The research was conducted at the Meteorology, Climatology and Geophysics Agency region 3 Denpasar using the software Tsunami Observation and Simulation Terminal (TOAST). The data used in this study is secondary data in the form of magnitude and data on the depth of underwater earthquakes, with magnitudes of 7.0 to magnitude 8.5 that have the potential to cause tsunamis and earthquake depth data of 18 km to 65 km. From the results of data processing with the TOAST application obtained the results of run-up and tsunami arrival time. Maximum run-up data was obtained by 9,718 m while the fastest tsunami arrival time data to the coast is 4 minutes after the tsunami. Maximum run-up data is then used for mitigation and the fastest tsunami arrival time then can be made a mitigation scenario for tsunami disaster.